Teaching Campus and Children's Legal Awareness : Character Education Innovation in Elementary Schools in Sekolah Dasar Wilayah 3T (Lembaga Pengembangan Kinerja Dosen, 2025)
The Campus Teaching Program is a concrete implementation of the Freedom to Learn policy, which positions students as agents of educational transformation in elementary schools, particularly in disadvantaged, frontier, and outermost (3T) areas. One fundamental problem faced by elementary schools in these areas is students' poor understanding of legal norms and school regulations. This condition contributes to high rates of disciplinary violations and rampant bullying behavior, such as verbal harassment, exclusion, and peer coercion. This study aims to analyze the contribution of the Campus Teaching Program in fostering legal awareness in elementary school students through a character education approach. The study used a qualitative approach with a case study method and was conducted at Budisari Public Elementary School, Cililin District, West Bandung Regency. Data were obtained through in-depth interviews with teachers, students, and student participants; participant observation during the learning process; and documentation of activities. Data validity was ensured through methodological triangulation and member checking techniques. The results indicate that the involvement of student teachers in the Campus Teaching Program facilitated the internalization of legal values through learning that integrates character education into both subjects and extracurricular activities. Students successfully developed various educational strategies, such as simulations of school regulations, role-plays about the consequences of violations, and group discussions on the values of honesty, responsibility, and mutual respect. The implementation of these activities resulted in increased student legal awareness, as evidenced by greater compliance with school regulations, fewer disciplinary violations, and a significant decrease in bullying incidents.